Mid-infrared carbon dioxide sensor with wireless and anti-condensation capability for use in greenhouses. Issue 6 (3rd July 2018) - Wang, J. N.; Xue, Q. S.; Lin, G. Y.; Ma, Q. J.
Abstract: A mid-infrared carbon dioxide sensor with wireless and anti-condensation capability was experimentally demonstrated for greenhouse application. The sensor included an optical module integrated in a multi-pass gas chamber using the dual-channel detection method to suppress environmental noise. Considering the condensation phenomenon in the greenhouse, the optical chamber was protected with a breathable waterproof coverage. The field test demonstrated that the internal optical framework was kept in stable relative humidity, ensuring the sensor's applicability in the greenhouse. For wireless communication, received signal strength indication was used to ensure the reliability of link quality and enable smart power regulation. In related experiments, there was a satisfying performance in terms of stability and error detection within the measurement range of 30 − 5000 ppm. Without increasing the integral time, the limit of detection of the sensor was at least 30 ppm, which was acceptable for greenhouse application. A field test was carried out in Town Shelin of Jilin Province, China and the test showed the proposed sensor had relatively good prospect for application in fine agriculture.